Revisiting the STEC Testing Approach: Using espK and espV to Make Enterohemorrhagic Escherichia coli (EHEC) Detection More Reliable in Beef - Delannoy, Sabine; Chaves, Byron D.; Ison, Sarah A.; Webb, Hattie E.; Beutin, Lothar; Delaval, José; Billet, Isabelle; Fach, Patrick (Frontiers in Microbiology, 2016)
Current methods for screening Enterohemorrhagic Escherichia coli (EHEC) O157 and non-O157 in beef enrichments typically rely on the molecular detection of stx, eae, and serogroup-specific wzx or wzy gene fragments. As these genetic markers can also be found in some non-EHEC strains, a number of ‘false positive’ results are obtained. Here, we explore the suitability of five novel molecular markers, espK, espV, ureD, Z2098, and CRISPRO26:H11 as candidates for a more accurate screening of EHEC strains of greater clinical significance in industrialized countries. Of the 1,739 beef enrichments tested, 180 were positive for both stx and eae genes. Ninety (50%) of these tested negative for espK, espV, ureD, and Z2098, but twelve out of these negative samples were positive for the CRISPRO26:H11 gene marker specific for a newly emerging virulent EHEC O26:H11 French clone. We show that screening for stx, eae, espK, and espV, in association with the CRISPRO26:H11 marker is a better approach to narrow down the EHEC screening step in beef enrichments. The number of potentially positive samples was reduced by 48.88% by means of this alternative strategy compared to the European and American reference methods, thus substantially improving the discriminatory power of EHEC screening systems. This approach is in line with the EFSA (European Food Safety Authority) opinion on pathogenic STEC published in 2013.